LMD-07. In Vitro AND In Vivo Culture of Patient Derived-Cerebral Spinal Fluid-Circulating Tumor Cells (PD-CSF-CTCs) in Leptomeningeal Disease (LMD) From Melanoma to Identify Novel Treatment Strategies. (9th August 2021) - Law, Vincent; Chen, Zhihua; Smalley, Inna; Vena, Francesca; Macaulay, Robert; Evernden, Brittany; Tran, Nam; Chen, Ann; Pina, Yolanda; Caceres, Gisela; Puskas, John; Duckett, Derek; et al.
Abstract: Background: Approximately 5% of melanoma patients (pts) will develop LMD. Currently there is no effective treatments for this disease. A significant barrier to the development of effective therapies has been the inability to culture CSF-CTCs for functional analysis. For the first time, we were able to successfully expand CSF-CTCs in vitro and in vivo . We assessed gene signatures of PD-CSF-CTCs to determine novel targets for therapy. As a proof of concept, we tested the efficacy of combining ceritinib (cer), an IGF-1R inhibitor and trametinib (tra), a MEK inhibitor, against LMD. Methods: CSF from 11 pts were collected from various sources (ie: LPs, Ommayas, rapid autopsies). PD-CSF-CTCs were expanded in vitro in conditioned media and in vivo using cell line-derived xenograft model. Single-cell RNA-sequencing (scRNAseq) analysis was performed to assess transcriptional profiles of PD-CSF-CTCs. Results: Of the total 61 PD-CSF-CTCs collected from 11 pts (avg: 4.07 CSF collections/patient), we successfully cultured PD-CSF-CTCs from 3 pts (20%) and were able to grow them in vivo from 2 pts (18%). scRNAseq identified IGF-1R, Sox9, ErbB3 and MLANA were among the enriched genes for PD-CSF-CTCs. IGF-1R inhibition by cer and depletion by CRISPR suppressed cell growth. We evaluated the responses of cer + tra treatment in vitro and found that combining these agents produced drug synergy against PD-CSF-CTCs and resensitized BRAF inhibitor-resistant melanoma cell line, WM164R. In vivo LMD xenograft model showed cer + tra treatment significantly prolonged median survival of PD-CSF-CTCs LMD (control: 27 days vs treatment: 38.5 days; P value < 0.032) and WM164R LMD (control: 35 days vs treatment: MS not reached; P value < 0.047). Conclusions: Though the sample size is small, this is the first report of the successful in vitro and in vivo culture of CSF-CTCs from pts with LMD.